2014
DOI: 10.1155/2014/739271
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Domain Optical Coherence Tomographic Findings of Bietti Crystalline Dystrophy

Abstract: We analyzed the OCT features of 24 eyes of 12 patients with Bietti crystalline dystrophy (BCD) with the Heidelberg HRA2-OCT. Seventeen of 24 eyes were in intermediate stage of the disease and seven in advanced stage of the disease at the time of latest OCT examination performed in 2014. Outer retinal tubulations and retinal hyperreflective dots were present in 20 of 24 eyes. The remaining four eyes had advanced disease with very thin retina. Appearance of bright plaque on top of RPE-Bruch membrane was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…Outer retinal tubulations have also been noted in a number of other inherited retinal degenerations, [67][68][69] but only Bietti crystalline retinopathy seems to show ORTs frequently. 70,71 Other studies have reported ORTs in CHM, 7,37,51,69,72 but the high frequency of this pathologic finding in our cohort leads to the suggestion that ORTs may be an expected part of the CHM phenotype. The presence of ORTs in patients at early ages suggests the effect is not simply a late-stage abnormality.…”
Section: Retinal Structure Following the Effects Of Rep1 Mutationscontrasting
confidence: 45%
“…Outer retinal tubulations have also been noted in a number of other inherited retinal degenerations, [67][68][69] but only Bietti crystalline retinopathy seems to show ORTs frequently. 70,71 Other studies have reported ORTs in CHM, 7,37,51,69,72 but the high frequency of this pathologic finding in our cohort leads to the suggestion that ORTs may be an expected part of the CHM phenotype. The presence of ORTs in patients at early ages suggests the effect is not simply a late-stage abnormality.…”
Section: Retinal Structure Following the Effects Of Rep1 Mutationscontrasting
confidence: 45%
“…These hyper‐reflective dots are not specific of IRD linked to MERTK mutations. They have also been reported in association with Stargardt disease (Ge et al., ), Bietti crystalline dystrophy, independently of crystal location (Saatci, Doruk, Yaman, & Oner, ), and RCD (Kuroda et al., ). In the latter, Kuroda et al.…”
Section: Clinical Characteristics Of Patients Carrying Mertk Mutationsmentioning
confidence: 82%
“…24,25 Optical Coherence Tomography Findings Spectral domain optical coherence tomography (SD-OCT) is able to provide detailed imaging of the retinal architectural changes in patients with BCD. [26][27][28][29][30][31] A myriad of hyperreflective spots of various configurations are present in SD-OCT sections of patients with BCD. 27,32 These multiple hyperreflective retinal dots have been observed in all retinal layers, including the inner retina and on top of the Bruch membrane.…”
Section: Fundus and Anterior Segment Features Of Bcdmentioning
confidence: 99%
“…17 Cystoid macular edema has also been observed in a few reported cases of BCD. 17,26,36 Fundus Autofluorescence Findings Fundus autofluorescence (FAF) imaging with confocal scanning laser ophthalmoscope imaging is derived from lipofuscin within the RPE, allowing noninvasive visualization of the RPE layer in BCD patients. 35 In the early stage of BCD, FAF reveals widespread hypoautofluorescence corresponding to areas of RPE atrophy and multiple hyperautofluorescent speckles in the fundus (Fig.…”
Section: Fundus and Anterior Segment Features Of Bcdmentioning
confidence: 99%
See 1 more Smart Citation